Human Lactobacillus Biosurfactants as Natural Excipients for Nasal Drug Delivery of Hydrocortisone - Elisa Corazza; Angela Abruzzo; Barbara Giordani; Teresa Cerchiara; Federica Bigucci; Beatrice Vitali; Massimiliano Pio di Cagno; Barbara Luppi (MDPI AG, 2022)
The inclusion of a chemical permeation enhancer in a dosage form is considered an effective approach to improve absorption across the nasal mucosa. Herein we evaluated the possibility of exploiting biosurfactants (BS) produced by Lactobacillus gasseri BC9 as innovative natural excipients to improve nasal delivery of hydrocortisone (HC). BC9-BS ability to improve HC solubility and the BS mucoadhesive potential were investigated using the surfactant at a concentration below and above the critical micelle concentration (CMC). In vitro diffusion studies through the biomimetic membrane PermeaPad® and the same synthetic barrier functionalized with a mucin layer were assessed to determine BC9-BS absorption enhancing properties in the absence and presence of the mucus layer. Lastly, the diffusion study was performed across the sheep nasal mucosa using BC9-BS at a concentration below the CMC. Results showed that BC9-BS was able to interact with the main component of the nasal mucosa, and that it allowed for a greater solubilization and also permeation of the drug when it was employed at a low concentration. Overall, it seems that BC9-BS could be a promising alternative to chemical surfactants in the nasal drug delivery field.